2019
DOI: 10.1111/cfs.12657
|View full text |Cite
|
Sign up to set email alerts
|

Providing a secure base for LGBTQ young people in foster care: The role of foster carers

Abstract: The experiences and needs of lesbian, gay, bisexual, trans and queer/questioning (LGBTQ) young people in care have been overlooked in England, in both policy and research. This paper reports on findings from the first study of LGBTQ young people in care in England and focuses on the nature of foster carers' experiences and perspectives on caring for LGBTQ young people. Qualitative interviews regarding the fostering role in caring for LGBTQ young people were conducted with a sample of foster carers (n = 26) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
3
13
0
1
Order By: Relevance
“…Although a research overview on LGBTQIA+ youth refers to them as 'a population with much more resilience than risk' (McCormick et al, 2017), this idea does not seem to be substantiated in much research. However, a handful of studies have uncovered the role of several resilience factors: the value of education in LGBTQ former foster youth (Capous-Desyllas & Mountz, 2019), the importance of social support among LGBTQ youth in transitional living shelters (Forge., 2012), the important role of foster carers' acceptance (McCormick et al, 2016) and carers' provision of nurturing relationships with youth (Schofield et al, 2019). It seems that LGBTQIA+ youth relationships with care practitioners and especially with foster carers are of utmost importance for their resilience development.…”
Section: Resilience Of Lgbtqia+ Youth In Carementioning
confidence: 99%
“…Although a research overview on LGBTQIA+ youth refers to them as 'a population with much more resilience than risk' (McCormick et al, 2017), this idea does not seem to be substantiated in much research. However, a handful of studies have uncovered the role of several resilience factors: the value of education in LGBTQ former foster youth (Capous-Desyllas & Mountz, 2019), the importance of social support among LGBTQ youth in transitional living shelters (Forge., 2012), the important role of foster carers' acceptance (McCormick et al, 2016) and carers' provision of nurturing relationships with youth (Schofield et al, 2019). It seems that LGBTQIA+ youth relationships with care practitioners and especially with foster carers are of utmost importance for their resilience development.…”
Section: Resilience Of Lgbtqia+ Youth In Carementioning
confidence: 99%
“…We know that the openness and willingness of practitioners to discuss sensitive issues with regard to embarrassment, stigma, and homophobic behavior is connected to successful professional support (Mallon et al, 2002;McCormick et al, 2017;Schofield et al, 2019). Child welfare organisations should therefore focus on ensuring a safe and supportive care environment for LGBTQIA+ youth, and support the practitioners working with them.…”
Section: Despite This Overrepresentationmentioning
confidence: 99%
“…And yes… that really did damage me so to say. Although most literature points to the rejection and discrimination experienced by LGBTQIA+ youth in care, some studies have shown that supportive and affirming practitioners are also to be found (e.g., Gallegos et., 2011;Ragg et al, 2006;Schofield et al, 2019). Foster family acceptance, families that are SOGIE-accepting and affirming, has also appeared as a key resource to improve the experiences of LGBTQIA+ young people (McCormick et al, 2016).…”
Section: Not Allmentioning
confidence: 99%
“…Вважаємо за доцільне включити перераховані вище теми в українську програму. Важливо також до неї додати інформацію щодо гендерних аспектів уразливості дівчат до ВІЛінфекції [28], виховання гендерно нонконформних підлітків у замісних сім'ях, психологічної підтримки у переживанні внутрішньої стигми та розв'язуванні ними проблем, пов'язаних зі стресом меншин [22].…”
Section: методологія роботиunclassified